Finance and development in Thailand - Rozental, Alek Aron. (New York ; London : Praeger Publishers, 1970)
The purpose of the study was threefold. In the first place, an attempt was made to contribute to the theory of economic growth. Secondly, the study was to provide the students of south East Asia in general, and of Thailand in particular, with a comprehensive description and analysis of the financial markets in an open dualistic economy of which Thailand is a prime example. Lastly, the study endeavours to provide the development planner in the field with specific and pragmatic suggestions for the improvement of the performance of financial intermediaries in Thailand.
Includes bibliographical references.
ne 22/01/2019
Loans
Keywords: Finance; Thailand